Operation, replacement and maintenance of sewers the sewers of London : a paper presented at a meeting of the British Tunnelling Society on 13th January 1977, at the Institution of Civil Engineers, Great George St., Westminster - Wroe, L. R. (Institution of Civil Engineers, 1977)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Paper presented at a BTS meeting on the operation, replacement and maintenance of sewers held on 13 January 1977.